2017
DOI: 10.1016/j.vaccine.2017.07.076
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between anthrax lethal toxin neutralizing antibody levels and survival in guinea pigs and nonhuman primates vaccinated with the AV7909 anthrax vaccine candidate

Abstract: The anthrax vaccine candidate AV7909 is being developed as a next generation vaccine for a post-exposure prophylaxis (PEP) indication against anthrax. AV7909 consists of the Anthrax Vaccine Adsorbed (AVA, BioThrax®) bulk drug substance adjuvanted with the immunostimulatory oligodeoxynucleotide (ODN) compound, CPG 7909. The addition of CPG 7909 to AVA enhances both the magnitude and the kinetics of antibody responses in animals and human subjects, making AV7909 a suitable next-generation vaccine for use in a PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Though technically demanding, TNA confirms previous exposure toB. anthracis in animals and is species-independent (Ngundi, Meade, Lin, Tang, & Burns, 2010;Omland et al, 2008;Savransky et al, 2017). On the other hand the ELISA assay detects antibodies to PA antigen in sera of infected individuals and is less demanding but well correlated with the TNA (Arciniega & Domínguez-Castillo, 2011;Ndumnego, Crafford, Beyer, & van Heerden, 2013;Parreiras, Sirota, Wagner, Menzies, & Arciniega, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Though technically demanding, TNA confirms previous exposure toB. anthracis in animals and is species-independent (Ngundi, Meade, Lin, Tang, & Burns, 2010;Omland et al, 2008;Savransky et al, 2017). On the other hand the ELISA assay detects antibodies to PA antigen in sera of infected individuals and is less demanding but well correlated with the TNA (Arciniega & Domínguez-Castillo, 2011;Ndumnego, Crafford, Beyer, & van Heerden, 2013;Parreiras, Sirota, Wagner, Menzies, & Arciniega, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Studies in guinea pigs and in non-human primates reported a correlation between anthrax lethal toxin neutralizing antibody levels and survival in animals vaccinated with Anthrax Vaccine Adsorbed (AVA) adjuvanted with CpG 7909 and challenged with B anthracis spores. 16 The AVA adjuvanted with CpG 7909 induced a rapid, highly protective immune response with the relatively low toxin neutralizing antibody levels associated with the high level of protection indicating that, in addition to antibodies, protection is also conferred by the B- and T-cell repertoire and other aspects of the immune response that are stimulated during immunization and restimulated upon challenge. In a phase 1 study, the addition of CpG 7909 to AVA increased the antibody response by 6- to 8-fold at peak and accelerated the response by 3 weeks when administered intramuscularly (IM) compared to the unadjuvanted vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Cynomolgus macaques inoculated with nebulized B. anthracis experienced significantly improved survival after receiving the novel tetracycline class antibiotic TP-271 88 . Survival of inhalational anthrax in this primate species was also significantly improved by administering a post-exposure prophylaxis vaccine, AV7909 89 . The combination of both post-exposure treatments was tested in rhesus macaques where antibiotics (ciprofloxacin × 14 days) and vaccine therapy (anthrax vaccine adsorbed, AVA) significantly improved post-exposure survival compared to antibiotics alone, likely due to delayed germination of anthrax spores occurring after completion of antibiotics leading to anthrax infection 90 .…”
Section: Nhp Models In Sepsis Therapymentioning
confidence: 99%
“…Other studies using rhesus or cynomolgus macaques administered aerosolized B. anthracis spores via nose- or head-only exposure chambers 8890 . Animals developed a moribund, disseminated anthrax infection with sepsis and respiratory failure over several days 88,89 . The inhalational model mimics the likely mechanism of exposure to B. anthracis (airborne dispersion) in a possible terrorist attack and is therefore invaluable to researchers developing novel anthrax therapies for such a public health emergency 90,91 .…”
Section: Organ-specific Models Of Sepsismentioning
confidence: 99%